PENERAPAN APLIKASI MOBILE BERBASIS GAME EDUKASI UNTUK PEMBELAJARAN TAJWID INTERAKTIF PADA SISWA MADRASAH IBTIDAIYAH - Mahgfirotin; Muhammad Kholil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of technology-based Tajweed educational game applications in learning the Qur'an Hadith in grade IV of Madrasah Ibtidaiyah Darussalam. This study also examines students' learning experiences, teachers' perspectives, and factors that support or inhibit their use. This study uses a descriptive qualitative approach with a case study design. Data collection methods include observation, interviews, questionnaires, and documentation. The collected data is then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the application can create a more interactive and student-focused Tajweed learning process with material features, audio pronunciation features, and interactive quizzes. This application has also been proven to increase motivation, participation, independence, and increase students' confidence in reading the Qur'an correctly according to the rules of tajweed. Teachers gave positive responses to the use of the application. As a learning support tool in the digital era, the use of this application is supported by student enthusiasm, attractive audio-visual displays, and guidance from teachers. However, some challenges still remain, such as limited devices, limited internet access, limited study time, and potential obstacles due to smartphone use.